Kinetic Study of Seed-Assisted Crystallization of ZSM-5 Zeolite in an OSDA-Free System Using a Natural Aluminosilicate as Starting Source - Corregidor, Pablo Fernando (2018)
We studied the crystallization of ZSM-5 zeolite by hydrothermal treatment in the absence of organic structure directing agents (OSDA) at 170, 180, and 190 °C, using Perlite as a natural source of SiO2 and Al2O3. Experimental data were fitted by nonlinear regression following the Kolmogorov-Johnson-Mehl-Avrami's nucleation/crystallization model in order to calculate kinetic constants (k), induction periods (t0), and Avrami's exponents (n). A constant value of n = 3.4 implicates the same mechanism in the studied range of temperature with a contribution from three dimensions to crystal growth and a nucleation that may include both sporadic and instantaneous mechanisms. Different stages of crystallization were clearly differentiated, and specific kinetics parameters were calculated. Compared with previously reported preparations, we found that the synthesis from Expanded Perlite is a promising alternative as it not only avoids the use of OSDA but also consumes less energy. Finally, a five steps crystallization mechanism has been proposed.